Successful, staged management of an iliac artery to ileal urinary conduit fistula - Laxmi Sistla, MBBS; Gert Frahm-Jensen, MBBS, FRACS (Journal of Vascular Surgery Cases and Innovative Techniques, 2023)
Fistula formation between the iliac artery and an ileal conduit is a rare pathology. A 39-year-old female patient presented with intermittent hematuria from her ileal conduit for 4 days, which progressed to massive hemorrhage on the ward. Her background includes stage 4A squamous cell carcinoma of the cervix treated with pelvic chemoradiotherapy and brachytherapy, recurrent obstructive uropathy requiring bilateral nephrostomies and bilateral ureteral stenting. Twelve months before this presentation, she had been treated for an iliac artery–ileal conduit fistula with a covered stent to the left common iliac artery. After initial fluid resuscitation, the bleeding was managed with endovascular placement of a covered stent. She subsequently underwent definitive vascular reconstruction with removal of the common iliac artery stents, an aortoiliac bypass using a vein graft, and repair of the ileal conduit electively. This case demonstrates the management of a rare clinical pathology and highlights the importance of close surveillance after endovascular procedures.